PHENOBARBITAL-INDUCED ERYTHEMA MULTIFORM: CASE REPORT - Teixeira Tinoco Rodrigues, Matheus; Coutinho Chequer Cabral, Gabriela; Andrea Marques Ferro, Ivis; Guardone Guimarães, Mariana; Lacerda Tinoco Boechat Cabral, Hildeliza (LINKSCIENCEPLACE, 2026)
This article discusses a case report in which the patient is affected by a cutaneous reaction identified as erythema multiforme after the use of the drug phenobarbital. Erythema multiforme is an acute, inflammatory alteration that occurs with erythematous and vesicullulosus papular lesions. This case report highlights the importance of the dermatological clinical examination associated with the patient's history for a diagnosis and early treatment, and emphasizes the importance of the patient to use any medication always guided by a professional.